Bibliometric Analysis in Mapping Corporate Marketing Research Trends and Developments - Maharani, Dewi; Yuswono, Irawan; Sutono, Sutono; Junianto, Pilifus (Westscience Press, 2023)
This research conducts a comprehensive bibliometric analysis to map the trends and developments in corporate marketing research, utilizing data from a diverse range of publications. Through theme analysis, influential publications, and keyword occurrences, the study unveils the multifaceted nature of the field. The most prevalent themes include Corporate Marketing, Green Marketing, Reputation, Communication, and Relationship Marketing, reflecting the dynamic interplay of strategic elements within corporate marketing. Noteworthy publications, such as